New Format for Steelband Festival - Blood, Peter Ray (Trinidad Guardian)
Twenty conventional steel orchestras are registered to participate, at the ninth edition of the biennial Pan is Beautiful Steelband Festival Series. Bands include 1973 champion Nutones, and 1980 winner Neal and Massy Trinidad All Stars. Unlike previous festivals, there will be no Test Piece for Pan is Beautiful IX.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Music festivals -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago